Examining the Self-Efficacy Levels of Nursing Students in Medication Administration for Children: A Quasi-Experimental Pre-test Post-test Study - Emine Bayrak Aykan (Acıbadem Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Purpose: This study aimed to examine the self-efficacy levels of nursing students in pediatric medication administration before and after receiving theoretical instruction on medication administration in children and completing clinical practice within the Pediatric Nursing course.Methods: This study adopted a quasi-experimental design with pre-test and post-test measurements. The study was conducted during 2024–2025 academic year with 63 third-year nursing students enrolled in the Pediatric Nursing course at Ankara Medipol University. Data were collected using the Socio-Demographic Information Form and the Nursing Student Self-Efficacy Scale for Pediatric Medication Administration. Differences were considered statistically significant at p < 0.05.Results: The educational intervention significantly increased the self-efficacy scores for pediatric medication administration (p